2010
DOI: 10.1097/smj.0b013e3181e6d3a7
|View full text |Cite
|
Sign up to set email alerts
|

Carcinomatous Meningitis Secondary to Transitional Cell Bladder Cancer

Abstract: We report a patient with carcinomatous meningitis secondary to known transitional cell carcinoma of the bladder. The patient presented with multiple focal neurological signs and symptoms. Diagnosis was suggested by magnetic resonance imaging and confirmed by analysis of the cerebrospinal fluid. He received whole brain radiotherapy despite a poor prognosis. To our knowledge, this is only the fifth reported case of neoplastic meningitis due to bladder cancer with confirmatory imaging and cytology and only the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In carcinomatous meningitis secondary to transitional cell carcinoma, the most common presenting symptoms reported are diffuse headache and mental status changes. 7 In a review of 22 reported cases, five had cranial nerve involvement, and all but one of these cases had cranial nerve VII involvement. 7 There have been no reports of carcinomatous meningitisassociated sensory hemineglect that we are aware of, but sensory disturbance is not uncommon.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…In carcinomatous meningitis secondary to transitional cell carcinoma, the most common presenting symptoms reported are diffuse headache and mental status changes. 7 In a review of 22 reported cases, five had cranial nerve involvement, and all but one of these cases had cranial nerve VII involvement. 7 There have been no reports of carcinomatous meningitisassociated sensory hemineglect that we are aware of, but sensory disturbance is not uncommon.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…7 In a review of 22 reported cases, five had cranial nerve involvement, and all but one of these cases had cranial nerve VII involvement. 7 There have been no reports of carcinomatous meningitisassociated sensory hemineglect that we are aware of, but sensory disturbance is not uncommon. The MRI and CSF examination of our patient was markedly abnormal, and this has been reported in a few cases of transitional cell carcinoma associated carcinomatous meningitis.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoadjuvant chemotherapy with cisplatin and gemcitabine was followed by radical cystectomy. Pathology case reports [7][8][9][10][11]. Our case represents a first case, to the best of our knowledge, of a patient presenting with both parenchymal intracranial as well meningeal metastasis in a patient with a history of urothelial carcinoma previously treated with surgery and adjuvant therapy, in the absence of any additional extracranial systemic metastasis.…”
Section: Casementioning
confidence: 99%
“…CM has been described in isolated case reports (2,3,13). Clinical course and neuroimaging findings have not been investigated in detail in the Chinese population.…”
Section: Duan H Et Al: Carcinomatous Meningitis In the Chinese Populmentioning
confidence: 99%